Association of Thyroid Function Test Values with Prepregnancy Body Mass Index and Gestational Weight Gain: A Systematic Review of Literature Reviews - Masoomeh Goodarzi-Khoigani; Tayebe Shojaddni Ardakani; Maryam Shirazi (Iranian Journal of Nursing and Midwifery Research)
Background: Gestational Weight Gain (GWG) is an important indicator affecting pregnancy outcome, and thyroid hormones are also weight regulators. Researchers showed that thyroid hormones were correlated to prepregnancy Body Mass Index (BMI) and GWG. However, the normal ranges of thyroid parameters and GWG depend on the trimester of measurement. Therefore, we systematically reviewed the current knowledge on the association between thyroid function tests and prepregnancy BMI and GWG. Materials and Methods: This review was finally conducted on nine articles, while Google Scholar and databases such as Scopus, Medline, Cochrane Library, ISI Web of Science, Science Direct, and ProQuest were searched to find English articles from October 2022 to June 2023. Results: Thyroid-Stimulating Hormone (TSH) was positively correlated with prepregnancy BMI, while Free Thyroxine (FT4) was inversely correlated. TSH was positively related to weight gain and BMI in the first trimester, while the relationship was negative for FT4. Free Triiodothyronine (FT3) had a positive relationship with BMI in the first trimester (p = 0.004). Furthermore, TSH level was not associated with GWG in the second and third trimesters, while FT4 was inversely correlated with GWG. FT3 also increased with BMI in the second trimester and not in the third trimester (p < 0.001). Finally, there was a positive correlation between thyroid peroxidase autoantibodies values and prepregnancy BMI as well as maternal BMI, but the data were inconsistent. Conclusions: Determining the relationship between thyroid hormone levels and prepregnancy BMI and/or GWG may help researchers and clinicians manage weight gain and/or thyroid function in pregnancy.